(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
Nigeria is a nation of three major religious groups that has different faith dynamism and practices. The history of Nigeria as a country will not be complete without a research on the issues currently threatening the peace of the nation. More so, over the years, the issue of the diversity in the ethnic groups and tribes has contributed to the division among Nigerians and has done more harm than good in fostering peace and unity in the country (Nweke 2018). Religious and ethnic sentiment has also contributed negatively to the growth and developmental sustainability of Nigerians a whole. What is Christian faith and doctrine? What constitutes the Christian doctrine? What are the teachings and values expected of a Christian in order to bring peace to the country? What role can Christian faith, teachings and practices play in the sustainability of peace in Nigeria? This paper provides succinct answers to these questions. The paper adopted a descriptive and analytical research approach. The research revealed that Christianity just like the other two religions in Nigeria is an advocate of peace and they it also creates a sense of dependence and oneness among human beings (Churchill & Michael 2023). The paper concludes that Christianity is an indispensable tool in sustaining peace in Nigeria since it comes with teachings and practices worth emulating. This paper recommends that people should be sensitized about the importance of sustaining peace in Nigeria. However, the effective teaching of religious studies and uplifting of moral and spiritual values by the religious leaders will go a long way to bring about peace in Nigeria.